Particle speed determination models in blasting - Pinto-Morales, Luis Humberto; Fuentes-Fuentes, María del Carmen (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
This is an exposition of the results obtained with the use of different particles speed models, used during the blasts carried out in the company "Calizas y Agregados Boyacá S.A.", in order to consider and to control the  vibrations generated by blasts are direct product of the use of explosives for the  damage's level caused by the execution of these works. This investgation was made with the aim to monitor the vibrations induced by the blasts on the structures and cosntructions of interest, near the final design line of the limestone quarry pit, that belongs to this company, in Sáchica, Boyacá.